Digital Games as a Context for Children's Cognitive Development: Research Recommendations and Policy Considerations. Issue 1 (15th April 2019) - Blumberg, Fran C.; Deater‐Deckard, Kirby; Calvert, Sandra L.; Flynn, Rachel M.; Green, C. Shawn; Arnold, David; Brooks, Patricia J.
Abstract: We document the need to examine digital game play and app use as a context for cognitive development, particularly during middle childhood. We highlight this developmental period as 6‐ through 12‐year olds comprise a large swath of the preadult population that plays and uses these media forms. Surprisingly, this age range remains understudied with regard to the impact of their interactive media use as compared to young children and adolescents. This gap in knowledge about middle childhood may reflect strong and widely held concerns about the effects of digital games and apps before and after this period. These concerns include concurrent and subsequent influences of game use on very young children's and adolescents' cognitive and socioemotional functioning. We highlight here what is currently known about the impact of media on young children and adolescents and what is not known about this impact in middle childhood. We then offer recommendations for the types of research that developmental scientists can undertake to examine the efficacy of digital games within the rapidly changing media ecology in which children live. We conclude with a discussion of media policies that we believe can help children benefit from their media use. Our hope is that this review will foster greater investigation of the cognitive socialization, as raised over 20 years ago by developmental psychologist and early games researcher Patricia Greenfield, that digital games serve during the middle childhood period, and childhood more generally. Abstract : Read the accompanying policy brief from SRCD